An Improved Energy Efficient Dynamic Cluster Head Selection in WSN with Inner and Border Nodes (International Journal of Current Engineering and Technology, 2015)
Wireless sensor networks are basically energy constraint network. Carrying the limited energy for longer time is thechallenge in hierarchical clustering algorithms. Clustering in WSN provides efficient way of utilizing energy toincrease the network lifetime. Applications of WSN are surveillance networks, military applications, disaster recoveryetc. In WSN, all nodes participate in cluster head selection which may give rise to death of border nodes very soon asborder nodes participate in cluster head selection and sensing the environment for data. To avoid this situation weproposed a method which divides the network into inner area nodes and border area nodes allowing only the innerarea nodes to participate in the cluster head selection. Hence this method not only increases the life time of bordernodes but also the entire network life time. The cluster heads are selected within the inner nodes, based on dynamiccluster head selection scheme. The proposed scheme uses the residual energy of each node to elect as cluster head, if itfinds multiple nodes with same residual energy then it considers cost values of those nodes to decide which node ismade as cluster head.
Keywords: Wireless sensor network; energy efficiency; lifetime; clustering; cluster-head; border nodes; inner nodes